White clover living mulch enhances soil health vs. annual cover crops. (27th July 2021) - Hill, Nicholas S.; Levi, Matthew; Basinger, Nicholas; Thompson, Aaron; Cabrera, Miguel; Wallace, Jason; Saikawa, Eri; Avramov, Alexander; Mullican, Jill
Abstract: Cover crops can improve soil health by increasing soil organic matter, soil porosity, permeability, and crop yield. Yet, land planted to cover crops are often limited by economic constraints. Perennial living mulch (LM) cover crops may provide better benefits to soil health because they are actively growing throughout the year and self‐regenerate without reseeding. The objective of this study was to compare the impact of a white clover ( Trifolium repens L.) LM vs. annual cover crops on soil health traits. Treatments were established on a Cecil sandy loam soil in the fall of 2014 and annual cover crop treatments re‐established each fall of the following 3 yr. White clover re‐established in the LM without reseeding. Corn ( Zea mays L.) was planted into the treatments in the spring of each year. Soils were sampled at the V4/V5, V12, and R5 stages of corn development and analyzed for chemical traits. Surface soil characteristics were measured after corn harvest in 2018. Soils in the LM system had lower lime buffering capacity and greater pH, base saturation, cation exchange capacity (CEC), Ca, K2 O, Mg, P2 O5, and total organic C concentrations than other treatments. Soil NH3 and NO3 had seasonal fluctuations associated with mineral N fertilizer and were lower in the LM treatment. After 3 yr, the soil bulk density was lower and porosity, water infiltration, and labile C were greater in surface soils from the LM treatment than in the surface soils of the other treatments. Use of a perennial LM cover crops expedited soil health regeneration compared to other treatments. Core Ideas: Cover crops improve soil quality. Living mulch cover crops are perennial and do not require annual re‐seeding. Soil physical characteristics improve faster in living mulch than annual cover crop systems. Mineral nutrients are retained in living mulch soils compared to annual cover crops. The living mulch system reduced yield.